Productivity and food security effects of using of certified seed potato: The case of Kenya's potato farmers - Okello, J.J.; Zhou, Y.; Kwikiriza, N.; Ogutu, S.; Barker, I.; Atieno, E.; Ahmed, J.T.; Schulte-Geldermann, Elmar (Springer, 2017)
Background: Potato is a major food crop in the tropical regions of Africa. However, potato yields continue to remain very low in these regions mainly due to use of poor quality seed. The recent development of rapid seed multiplication technique has helped to shorten the duration of certified seed potato (CSP) production and increase the supply of seed. This study assessed the effect of using CSP on yield, input use, and food security among smallholder farmers. It focused on potato growers in central highlands of Kenya, who were in close proximity to a private seed multiplier that uses these new techniques. The study used the propensity score matching technique and data collected from 408 smallholder farmers through personal interviews. The farmers were stratified by use of CSP. Results: The study found positive effect of using certified seed on both yield and food security. There was also a slight increase in input usage, apparently due to pursuit by farmers to optimize the gains from CSP. Conclusion: The study concludes that using CSP has positive effect on smallholder farm households.